2022
DOI: 10.3390/polym14112280
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Efficient Alkali Treatment and the Effect of Flame Retardant on the Mechanical and Fire Performance of Frost-Retted Hemp Fiber Reinforced PLA

Abstract: : This research investigates an effective alkali (NaOH) treatment and fire-retardant coating to produce biocomposites from frost-retted hemp fiber and PLA. The fiber surface treatment with various NaOH concentrations was investigated throughout a range of soaking times. The results show that the extracted non-cellulosic fiber content increases with treatment duration and NaOH concentration, while the fraction of targeted components removed remains nearly unchanged after soaking for 1, 2, and 4 h with a 5 wt.% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Moreover the aging slightly induce the flame propagation speed in temperature exposed composites. This is because of thermally broken aged silane molecules allows the composite to capture fire and permits to propagate further 34 . It is noted that the thermally aged composites gives higher propagation speed than the water aged composites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover the aging slightly induce the flame propagation speed in temperature exposed composites. This is because of thermally broken aged silane molecules allows the composite to capture fire and permits to propagate further 34 . It is noted that the thermally aged composites gives higher propagation speed than the water aged composites.…”
Section: Resultsmentioning
confidence: 99%
“…This is because of thermally broken aged silane molecules allows the composite to capture fire and permits to propagate further. 34 It is noted that the thermally aged composites gives higher propagation speed than the water aged composites. Composite APR2 gives 12.63 mm/min whereas composite APH2 gives 12.32 mm/min.…”
Section: Flammabilitymentioning
confidence: 99%
“…For example, a previous study on the hemp fiber used in the current research found no significant difference in the mass loss, ignition time, temperature transfer through depth, basic protection time, or the start of char time for the composites with either untreated or alkali modified fibers [ 14 ], which is primarily due to the hemp fiber’s inherently low lignin content (1.4%) [ 15 ]. Despite this, considerable improvements in the mechanical characteristics [ 15 , 16 ], water absorption, and hygroscopic properties [ 14 ] of the composites were documented following alkali treatment. The biggest issue due to fire-retardant treatments of natural fibers is the loss of mechanical qualities [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, considerable improvements in the mechanical characteristics [ 15 , 16 ], water absorption, and hygroscopic properties [ 14 ] of the composites were documented following alkali treatment. The biggest issue due to fire-retardant treatments of natural fibers is the loss of mechanical qualities [ 16 ]. As a result, the challenge is to treat the fibers in a way that delivers both sufficient reaction to fire and mechanical and water sorption durability.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated biodegradable fibers as reinforced composites that exhibit superior performance and suitability for widespread use. Such composites combine the properties of the matrix polymer and reinforced fiber, and are lightweight and high strength [10][11][12]. The matrix material and reinforced fiber must meet the needs of engineering.…”
Section: Introductionmentioning
confidence: 99%